Toxic effects of crude root extract of Plumbago rosea (Rakta chitraka)on mice and rats - Solomon, F.E.; Sharada, A.C.; Devi, P.U.
The ethanolic root extract of Plumbago rosea (Plumbaginaceae)was studied for acute toxicity in mice and subacute toxicity in rats. The 24 h LD50 values of the extract in mice were 239.88 mg and 1148.15 mg/kg b. wt. for intraperitoneal and oral routes, respectively. Oral administration of doses above 1250 mg/kg produced severe diarrhea. In subacute toxicity studies no mortality was observed when 50 mg/kg of the extract was injected i.p. daily for 30 days; however, there was no weight gain in the treated rats. Significant reduction in the weights of liver, kidney, thymus and testes was observed in the male rats, while the spleen weight showed a significant increase from control. The females showed a significant loss in thymus weight and a gain in the weight of the uterus, but the liver and spleen did not show any weight change from the control. There was a significant increase in total WBC and neutrophil counts as well as in the levels of serum alkaline phosphatase and alanine transaminase (ALT)in both sexes. Similarly, the liver alkaline phosphatase level was significantly higher than control, but a significant reduction was observed in the DNA, RNA and total proteins. Thus, a higher drug dose (total dose of 15 g/kg b. wt.)was tolerated in fractionated administration, but it had a growth inhibitory effect in both sexes. The males appear to be more susceptible than females when individual organs are considered.
Keywords: ALANINE AMINOTRANSFERASE; ALKALINE; PHOSPHATASE; DNA; PLANT EXTRACT; PLUMBAGIN; PROTEIN; RNA